2002
DOI: 10.1088/1126-6708/2002/12/006
|View full text |Cite
|
Sign up to set email alerts
|

Landau-Pomeranchuk-Migdal resummation for dilepton production

Abstract: We consider the thermal emission rate of dileptons from a QCD plasma in the small invariant mass (Q 2 ∼ g 2 s T 2 ) but large energy (q 0 > ∼ T ) range. We derive an integral equation which resums multiple scatterings to include the LPM effect; it is valid at leading order in the coupling. Then we recast it as a differential equation and show a simple algorithm for its solution. We present results for dilepton rates at phenomenologically interesting energies and invariant masses.SPhT-T02/150, LAPTH-946/02 * A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
179
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(188 citation statements)
references
References 37 publications
9
179
0
Order By: Relevance
“…bremsstrahlung [15]. Around the lightcone the loop expansion breaks down due to the Landau-Pomeranchuk-Migdal effect and an infinite series of ladder diagrams contribute at leading order in the strong coupling constant [16,17]. Finally for very soft momenta and energies, the structure of currentcurrent spectral functions is determined by general hydrodynamical considerations [18].…”
Section: Continuummentioning
confidence: 99%
“…bremsstrahlung [15]. Around the lightcone the loop expansion breaks down due to the Landau-Pomeranchuk-Migdal effect and an infinite series of ladder diagrams contribute at leading order in the strong coupling constant [16,17]. Finally for very soft momenta and energies, the structure of currentcurrent spectral functions is determined by general hydrodynamical considerations [18].…”
Section: Continuummentioning
confidence: 99%
“…This finds its manifestation in a too rapid rise of the spectral density which, in turn, leads to an infrared divergent Euclidean correlator of the vector current [13]. This low invariant mass regime has been examined in much detail [14,15] and it has been demonstrated that the spectral function at low energies will increase linearly with energy giving rise to a finite, non vanishing electrical conductivity of the quark gluon plasma. Lattice calculations of Euclidean time correlation functions can give access to spectral functions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Its treatment require the resummation of an infinite number of ladder exchanges of spacelike HTL gluons. This has been done for photons first [12] and later extended to small-M dileptons [13]. In the latter case it is important to note that the Born term in Fig.…”
Section: Nlo At Small Mmentioning
confidence: 99%